Designing the strategic model of online banking relational marketing in the fourth industrial revolution with the foundation's data approach. - Aliasghar Atarodi; arezo ahmadi danyali; nader gharib nawaz (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of this research is to design a strategic model of online banking relational marketing in the fourth industrial revolution with a data-based approach. The research method is applicable-developmental in terms of its purpose, and exploratory in terms of its nature. The statistical population of the research included 11 experts from the banking industry, and the sampling was done in a purposeful and snowball type. Data-based theory was used to collect and analyze data. The data collection tool is a semi-structured interview. Data analysis and model design were done in three stages of open, central and selective coding. The findings showed that emerging behaviors and new developments in relational marketing are key causal conditions, while the development of relational marketing components, customer behavior changing, and the fourth industrial revolution were identified as ground conditions. This study also showed the need for banking transformations, external disruptions, relationship management and human capital transformation, and barriers to online banking as intervener factors. Tactical transformative programs in the open banking system, using customer data for banking strategy, opportunism and loyalty with a constructivist perspective were identified as effective strategies. The consequences of this model include the transformation of the banking system and new banking, investing in new forms, increasing income by aligning online services, and managing relationships with virtual customers. Extended Abstract Introduction The first industrial revolution changed life and economy in general and changed the agricultural economy to an economy in which industry and machines are dominated by humans. Oil and electricity facilitated mass production in the second industrial revolution, and information technology was used to automate production in the third industrial revolution. Finally, in the fourth industrial revolution, attention was paid to increasing the cognitive power of human productions and this power was strengthened (Xu et al., 2018). Considering the fourth industrial revolution and the decline of traditional marketing and the emergence of relational marketing, organizations are determined to create strong links with their customers by using relational marketing strategies. Relational marketing is today's business art (Talari & Khoshroo, 2022). Online banking relational marketing is one of the important factors in the fourth industrial revolution. Due to the advancement of information and communication technology, banks need to find new ways to attract and retain their customers. In this regard, the use of online relational marketing methods can be effective in providing customers with a positive banking experience. Currently, the business environment is witnessing deep and fundamental changes, and many experts in the field of business and economics believe that this evidence indicates the beginning of a new era, the fourth industrial revolution (Basyazicioglu & Karamostafa, 2018). The first industrial revolution changed life and economy in general and changed the agricultural economy to an economy in which industry and machines are dominated by humans. Oil and electricity facilitated mass production in the second industrial revolution, and information technology was used to automate production in the third industrial revolution. Finally, in the fourth industrial revolution, attention was paid to increasing the cognitive power of human productions and this power was strengthened (Xu et al, 2018). Based on this, the current research is looking for an answer to this question: What is the strategic model of online banking relational marketing in the fourth industrial revolution with the data-based approach? Theoretical Framework Relational marketing Relational marketing consists of Creating, maintaining, and promoting relationships with customers and stakeholders of the company, which is achieved through building trust as a result of fulfilling obligations. In fact, relational marketing is defined as a type of marketing that attracts, develops, maintains, and promotes relationships with customers. The rationale for using relational marketing is that it forces the company to focus on the long-term financial benefits that can occur when a customer first enters the organization, and this is because acquiring new customers for the company is 5 to 10 times more expensive than retaining existing customers (Ghosal et al, 2020). Principles of marketing in the fourth industrial revolution Apart from the design principles of the fourth industrial revolution, marketing throughout the new industrial revolution has been accompanied by redefined marketing principles based on connectivity, communication, and collaboration in the digital ecosystem. Unlike traditional marketing, where marketers and organizations are in control, Industry 4.0 requires that all stakeholders—including customers, business partners, and suppliers—in the digital ecosystem be treated equally (Ramadhani et al, 2019). The main empowering technologies of the fourth industrial revolution in marketing Emerging technologies provide opportunities for companies to change their practices and adapt them to customer demands and expectations. Therefore, with new technologies in Industry 4.0, companies can achieve the sustainable competitive advantage needed for better market positioning and performance (Jančíková et al, 2019). Pfajfar et al, (2022) conducted a research entitled the value of corporate social responsibility for multiple stakeholders and social impact - relationship marketing perspective. The results confirm a positive relationship between employee-oriented CSR and the perceived usefulness of CSR actions for society, customers, and employees (but not suppliers). Differences between small and medium-sized companies and large B2B companies are observed with contrasting perceptions of relationship quality antecedents and outcomes. Rosário et al, (2022) conducted a research titled Industry 4.0 and Marketing: Towards an Integrated Future Research Agenda. This paper shows that there are several research avenues for marketing researchers to conduct research in, but the most important areas are the five principles of marketing in Industry 4.0: collaboration, dialogue, co-creation, recognition, and connection. Future research should focus on the quantitative study of these five principles. Research methodology The research method is applicable-developmental in terms of its purpose, and exploratory in terms of its nature. The statistical population of the research included 11 experts from the banking industry, and the sampling was done in a purposeful and snowball type. Data-based theory was used to collect and analyze data. The data collection tool is a semi-structured interview. Research findings Data analysis and model design were done in three stages of open, central and selective coding. The findings showed that emerging behaviors and new developments in relational marketing are key causal conditions, while the development of relational marketing components, customer behavior changing, and the fourth industrial revolution were identified as ground conditions. This study also showed the need for banking transformations, external disruptions, relationship management and human capital transformation, and barriers to online banking as intervenor factors. Tactical transformative programs in the open banking system, using customer data for banking strategy, opportunism and loyalty with a constructivist perspective were identified as effective strategies. The consequences of this model include the transformation of the banking system and new banking, investing in new forms, increasing income by aligning online services and managing relationships with virtual customers. Conclusion The current research was conducted with the aim of designing a strategic model of online banking relational marketing in the fourth industrial revolution with the data-based approach. The results of this research are in agreement with the results of Pfajfar et al, (2022), Rosário et al, (2022), Talari & Khoshroo (2022), Adetyoa et al., (2021), Zalkani Andarvar (2021), Mohammadi fateh et al, (2022), Najafzadeh Ziaodin et al, (2021), Mosavi et al, (2020), Vazifehdoust et al, (2017), and Kosiba et al, (2018). Mohammadi fateh et al, (2022) showed that the technologies of the fourth industrial revolution are big data, biological identification system, fraud detection technologies, contactless ATM, data mining, cloud computing, marketing, versatile channel, artificial intelligence, fintech, biometrics, blockchain, intelligent social networks, artificial neural networks, remote monitoring technologies, commercial Internet of Things, and digital account, respectively. Then, by these experts, the application rate of these technologies is specified in four areas of banking, i.e. marketing, human resource, risk management, and customer orientation in a three-level spectrum (low, medium and high). According to the opinion of experts, all the identified technologies have medium to high application in four areas of banking. According to the results of the research, the following suggestions are presented: It is suggested that online relational marketing is one of the important aspects of banking in the fourth industrial revolution. Online relational marketing can improve customer loyalty. To manage relationships with virtual customers, banks must use the principles of marketing in the fourth industrial revolution, including collaboration, dialogue, co-creation, recognition and connection. These principles create an innovative approach to the marketing mix under new conditions in the fourth industrial revolution.